2014
DOI: 10.1002/ajpa.22636
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the evolution of the windlass mechanism of the human foot from comparative anatomy: Insights, obstacles, and future directions

Abstract: Humans stand alone from other primates in that we propel our bodies forward on a relatively stiff and arched foot and do so by employing an anatomical arrangement of bones and ligaments in the foot that can operate like a "windlass." This is a significant evolutionary innovation, but it is currently unknown when during hominin evolution this mechanism developed and within what genera or species it originated. The presence of recently discovered fossils along with novel research in the past two decades have imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 84 publications
0
34
0
Order By: Relevance
“…Hunter‐gatherers display an enlarged talar neck and more rounded, broader navicular facets. It is known that, during toe‐off, transmission of body weight shifts from the talar head to the first and second metatarsals (Griffin et al, ; Jashashvili, Dowdeswell, Lebrun, & Carlson, ). Trinkaus () showed that unshod Native Americans have more robusticity in hallucal proximal phalanges compared to habitually shod Inuit and modern Euroamericans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hunter‐gatherers display an enlarged talar neck and more rounded, broader navicular facets. It is known that, during toe‐off, transmission of body weight shifts from the talar head to the first and second metatarsals (Griffin et al, ; Jashashvili, Dowdeswell, Lebrun, & Carlson, ). Trinkaus () showed that unshod Native Americans have more robusticity in hallucal proximal phalanges compared to habitually shod Inuit and modern Euroamericans.…”
Section: Discussionmentioning
confidence: 99%
“…However, different substrates may require different mechanisms (i.e., talar configurations) to achieve effective stability, for example navigating on uneven terrain versus asphalt roads may create different loading patterns. Moreover, the talus facilitates plantar‐ and dorsal flexion, as well as inversion‐eversion of the foot (Griffin, Miller, Schmitt, & D'Août, ; Huson, ). How these ankle motions could be influenced by the use of restrictive shoes is still an open question (D'Août et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a longitudinal arch is reflected in the geometric relationships among the bones of the human foot and ankle (DeSilva and Throckmorton, 2010;Ward et al, 2011;Prang, 2015b), including the declination of the talar head relative to the plane of the talocrural joint (Day and Wood, 1968;Peeters et al, 2013) and the declination of the calcaneocuboid joint relative to its proximodistal axis (Aiello and Dean, 1990;Prang, 2015b). Humans also possess soft tissue specializations associated with the longitudinal arch, such as a well-developed plantar aponeurosis, calcaneonavicular ligament, and long plantar ligament (Gomberg, 1981(Gomberg, , 1985, which all contribute to midtarsal stabilization via the 'windlass mechanism' (Hicks, 1954; reviewed by Griffin et al, 2015). Other primates lack these hard and soft tissue specializations and instead have much more mobile feet that are probably adapted for varying degrees of arboreal and terrestrial locomotion (e.g., DeSilva, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…333 naviculars are incompatible with the presence of a longitudinal arch, then they could belong to a species other than A. afarensis. Since significant hallucal abduction (e.g., as seen in extant African apes) is functionally incompatible with the 'windlass mechanism' associated with the longitudinal arch (Hicks, 1954;Griffin et al, 2015), and thus necessarily reflective of a flat foot, a candidate taxon for the A.L. 333 naviculars could be the one to which the BRT-VP-2/73 foot belongs.…”
Section: Introductionmentioning
confidence: 99%
“…A more dorsally projecting metatarsal (MT) head is thought to increase the dorsiflexion range of motion (ROM) at the MTPJs DeSilva et al, 2012). This increased ROM serves to stabilize the forefoot and aids propulsion at the end of stance phase by tightening the plantar aponeurosis, which is a fibrous band that originates from the calcaneal tuberosity and inserts distally on the proximal phalanges (DeSilva, 2010;Griffin et al, 2015). This tightening of the plantar aponeurosis has been likened to a "windlass mechanism" (Hicks, 1954;Bojsen-Møller, 1979;Susman, 1983;Griffin and Richmond, 2010;Griffin et al, 2015) wherein it is analogous to a cable, the metatarsal head a drum, and the proximal phalangeal base a handle.…”
Section: Introductionmentioning
confidence: 99%